2010
DOI: 10.1371/journal.pone.0014252
|View full text |Cite
|
Sign up to set email alerts
|

Depression and HIV in Botswana: A Population-Based Study on Gender-Specific Socioeconomic and Behavioral Correlates

Abstract: BackgroundDepression is a leading contributor to the burden of disease worldwide, a critical barrier to HIV prevention and a common serious HIV co-morbidity. However, depression screening and treatment are limited in sub-Saharan Africa, and there are few population-level studies examining the prevalence and gender-specific factors associated with depression.MethodsWe conducted a cross-sectional population-based study of 18–49 year-old adults from five districts in Botswana with the highest prevalence of HIV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 49 publications
12
79
1
1
Order By: Relevance
“…Individuals with total score 4 1.75 were considered to have probable depression. The HSCL-25 has widely been used in studies among refugees in many countries including Nigeria (Gupta et al, 2010;Aniebue and Onyema, 2008;Kleijn et al, 2001).…”
Section: Study Instrumentsmentioning
confidence: 99%
“…Individuals with total score 4 1.75 were considered to have probable depression. The HSCL-25 has widely been used in studies among refugees in many countries including Nigeria (Gupta et al, 2010;Aniebue and Onyema, 2008;Kleijn et al, 2001).…”
Section: Study Instrumentsmentioning
confidence: 99%
“…Nair et al [52] reported that Perceived Social Support was correlated with vitality (r = 0.28, p < 0.01) and mental health (r = 0.26, p < 0.01), suggesting that high levels of social support from family and friends are related to good mental health in the participants. Gupta et al [53] reported that depression was associated with stigma and relationship problems. Nair et al also reported how a low score on the SF-36 Bodily Pain Scale was associated with compromised ability to work.…”
Section: Linkages Among Impairment Activity and Participation Levelsmentioning
confidence: 99%
“…Numerous studies and reports have uncovered that these poor urban communities experience high rates of communicable (e.g., HIV) and, non-communicable diseases (e.g., respiratory disease, waterborne diseases, diabetes, stroke), injuries, and premature death (Ali, 2010;Butala et al, 2010;Kyobutungi et al, 2008;Sverdlik, 2011). The growing awareness that mental illness, particularly depression, is a tremendous contributor to the growing burden of disease worldwide, and especially in developing regions (Bird et al, 2010;Gupta et al, 2010;Izutsu et al, 2006;Lund et al, 2010;Prince et al 2007), suggests that improving wellbeing among slum dwellers, a charge of the Millennium Development Goals (MDGs), requires significantly more attention to mental health outcomes than the few existing studies have given.…”
Section: Introductionmentioning
confidence: 99%